2007
DOI: 10.1038/nn1873
|View full text |Cite
|
Sign up to set email alerts
|

Premotor cortex modulates somatosensory cortex during voluntary movements without proprioceptive feedback

Abstract: Movement perception relies on sensory feedback, but the involvement of efference copies remains unclear. We investigated movements without proprioceptive feedback using ischemic nerve block during fMRI in healthy humans, and found preserved activation of the primary somatosensory cortex. This activation was associated with increased interaction with premotor cortex during voluntary movements, which demonstrates that perception of movements relies in part on predictions of sensory consequences of voluntary move… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
132
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(150 citation statements)
references
References 13 publications
15
132
0
3
Order By: Relevance
“…Our findings are in agreement with previous studies that demonstrate enhanced evoked activity to self-generated stimuli in auditory (Reznik et al, 2014), somatosensory (Simões-Franklin et al, 2011;Ackerley et al, 2012), and visual (Hughes and Waszak, 2011) cortices compared with otherwise identical sensory stimuli perceived in a passive manner. These studies suggest that an efference copy enhances the neural response evoked by the sensory consequences of self-generated actions (see also Christensen et al, 2007). Other studies report attenuated responses to self-generated stimuli and suggest a canceling role of an efference copy in sensory cortices (Blakemore et al, 1998;Martikainen et al, 2005;Aliu et al, 2009;Baess et al, 2009;Saupe et al, 2013;Horváth, 2014;Timm et al, 2014).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our findings are in agreement with previous studies that demonstrate enhanced evoked activity to self-generated stimuli in auditory (Reznik et al, 2014), somatosensory (Simões-Franklin et al, 2011;Ackerley et al, 2012), and visual (Hughes and Waszak, 2011) cortices compared with otherwise identical sensory stimuli perceived in a passive manner. These studies suggest that an efference copy enhances the neural response evoked by the sensory consequences of self-generated actions (see also Christensen et al, 2007). Other studies report attenuated responses to self-generated stimuli and suggest a canceling role of an efference copy in sensory cortices (Blakemore et al, 1998;Martikainen et al, 2005;Aliu et al, 2009;Baess et al, 2009;Saupe et al, 2013;Horváth, 2014;Timm et al, 2014).…”
Section: Discussionmentioning
confidence: 91%
“…The magnitude of such modifications in sensory cortices has been previously reported to be mediated by the amount of motor output (Cui et al, 2014), and its source is believed to lie within the motor system, although its exact origin remains unknown. One study points to the ventral pre-motor cortex as a candidate brain region providing efferent signals to somatosensory cortex (Christensen et al, 2007), while other studies point to the cerebellum (Blakemore et al, 1998;Knolle et al, 2012Knolle et al, , 2013). Yet another study suggests the involvement of supplementary motor area (SMA; Haggard and Whitford, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Right ventral premotor cortex is an area that has been shown to modulate primary somatosensory cortex activations (Christensen et al, 2007) and right orbital frontal cortex is thought to represent anticipatory activity related to the expected sensory consequences of sensorimotor tasks (Schoenbaum et al, 2009). The right hemispheric nature of these and other correlated regions in this study aligns well with both our previous proprioceptive mapping work (Goble et al, 2011) and that of colleagues (2005, 2007), who found right hemisphere dominance for muscle spindle feedback processing.…”
Section: Discussionmentioning
confidence: 99%
“…Using ischaemic nerve block it has been shown that during voluntary movement, functional magnetic resonance imaging (fMRI) signal in primary somatosensory cortex (S1) is enhanced (even in the lack of sensory feedback) and functional connectivity with pre-motor cortex is increased, suggesting an enhancing effect of a motor efference copy 19 . Similarly, using positron-emission tomography it has been shown that increases in speech production rate result in increased cerebral blood flow in auditory cortices even when auditory feedback was blocked by white noise that was kept constant across rates 20 .…”
mentioning
confidence: 99%